"Times are altered with us": american indians from contact to the new republic - Carpenter, Roger M (The American History Series, 2015)
"Times Are Altered with Us": American Indians from Contact to the New Republic offers a concise and engaging introduction to the turbulent 300-year-period of the history of Native Americans and their interactions with Europeans-and then Americans-from 1492 to 1800. Considers the interactions of American Indians at many points of "First Contact" across North America, from the Gulf of Mexico to the Pacific and Atlantic Coasts Explores the early years of contact, trade, reciprocity, and colonization, from initial engagement of different Indian and European peoples-Spanish, French, Dutch, English, and Russian-up to the start of tenuous and stormy relations with the new American government Charts the rapid decline in American Indian populations due to factors including epidemic Old World diseases, genocide and warfare by explorers and colonists, tribal warfare, and the detrimental effects of resource ruination and displacement from traditional lands Features a completely up-to-date synthesis of the literature of the field Incorporates useful student features, including maps, illustrations, and a comprehensive and evaluative Bibliographical Essay Written in an engaging style by an expert in Native American history and designed for use in both the U.S. history survey as well as dedicated courses in Native American studies.